إدارة الوقت وعلاقته بجودة حياة العمل دراسة ميدانية بمقر بلدية بوسعادة - بوزيدي مسعودة; اشراف: شبيلي وهيبة (جامعة محمد بوضياف -المسيلة, 2025)
تهدف الدراسة الى التعرف والكشف عن العلاقة بين إدارة الوقت وجودة حياة العمل داخل المنظمة، ولتحقيق هذا الهدف تم استخدام المنهج الوصفي بأسلوب تحليلي وباستخدام الاستبيان كأداة لجمع البيانات مع المبحوثين في المؤسسة محل الدراسة وتم تحليلها بواسطة برنامج SPSS v25. تمت الدراسة الميدانية بمصلحة التنظيم والشؤون العامة ببلدية بوسعادة علـى جميع موظفي المصلحة، وبلغت 100 مفردة، وتوصلت الدراسة إلى: – وجود علاقة قوية طردية وبين عمليات إدارة الوقت وجودة حياة العمل. – وجود علاقة ضعيفة وعكسية بين مضيعات الوقت وجودة حياة العمل. – وجود علاقة متوسطة طردية وبين إدارة الوقت وجودة حياة العمل. كما خلصت الدراسة الى أن الاهتمام بأبعاد إدارة الوقت (التخطيط، التنظيم، التوجيه، الرقابة) يرفع من جودة حياة العمل لديهم، كلما كان هناك مضيعات للوقت يصاحبه انخفاض في جودة حياة العمل الكلمات المفتاحية: إدارة الوقت، التخطيط، التنظيم، التوجيه، الرقابة، جودة حياة العمل. Abstract: The study aims to identify and reveal the relationship between time management and the quality of work life within the organization. To achieve this goal, the descriptive approach was used in an analytical manner and using the questionnaire as a tool to collect data with the respondents in the institution under study, and it was analyzed using the SPSS v25 program. The field study was conducted by the Department of Organization and Public Affairs in the municipality of Bou Saada on all employees of the department, and it amounted to 100 individuals, and the study concluded: - There is a strong direct relationship between time management processes and quality of work life. - There is a weak and inverse relationship between time wasters and quality of work life. - There is a direct average relationship between time management and quality of work life. - The study also concluded that paying attention to the dimensions of time management (planning, organization, direction, control) increases the quality of their work life, whenever there is a waste of time accompanied by a decrease in the quality of work life Keywords: time management, planning, organization, direction, control, quality of work life.